The relationship between psychophysiological indicators and hormonal levels in elite wrestlers - Rossokha, Halyna; Vdovenko, Nataliia; Husarova, Anna; Maidaniuk, Olena; Kolodiazhna, Larysa; Kozak, Iryna (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This experimental study aimed to investigate the relationship between psychophysiological characteristics and the levels of the testosterone and cortisol hormones in elite athletes. Twenty elite Greco-Roman wrestlers (aged 20–33 years) from the Ukrainian national team participated in the study, with a total of 40 examinations conducted. The athletes had experience competing at World, European, and Olympic Championships. The concentration of testosterone and cortisol was determined in blood serum using an enzyme-linked immunosorbent assay, ChemWell (Awareness Technology, USA). Psychophysiological parameters were investigated using the "NS-Psychotest" computer system for psychophysiological evaluation, developed by Ukrmedspectr in Ukraine. A correlation analysis between the obtained endocrine and neurodynamic indicators showed a significant relationship (p<0.05) between testosterone levels and complex visual-motor reactions, cortisol levels, and the number of reactions delayed in the test of response to a moving object. For further analysis, athletes were divided into two groups according to the speed of sensorimotor response. The groups significantly differed (p<0.05) in the level of complex visual-motor reactions but did not significantly differ in simple reaction-time tests (p>0.05). In addition, differences in hormone levels between these groups were found. Thus, athletes with a better complex visual-motor reaction had significantly higher testosterone levels and lower cortisol levels. Research on the relationship between hormonal and psychophysiological markers may improve athlete monitoring and enable early detection of excessive stress responses.